KARAKTERISASI ARANG CANGKANG KELAPA SAWIT SEBAGAI BAHAN PEMBANTU UNTUK MINGKATKAN KESUBURAN TANAMAN BERDASARKAN KROMATOGRAFI GC – MS - Zainal Abidin Nasution; Harry P. Limbong (Balai Besar Industri Hasil Perkebunan, 2019)
In 2015, the area of oil palm plantations in Indonesia had reached 10,701,436 ha, with details of the people's oil palm plantation 4,810,271 ha, state-owned oil palm plantations 704,094 ha and private oil palm plantations 5,207,071 ha. A ton base of fresh palm oil fruit bunches will produce 20% - 23% CPO; 5% - 7% PKO and the rest in the form of solid waste, namely 20% - 23% oil palm empty bunches; 10% - 12% oil palm fruit fiber and 7% - 9% oil palm shells.In the implementation of this study, oil palm shell charcoal was made by treating palm oil shells. From the treatment of oil palm shell roasting, the average yield was 38.20% (the last temperature of roasting 348 0 C, when the palm shells being roasted were no longer smoke).From the results of the chromatogram analysis of GC - MS, oil palm shell charcoal is known as 25 organic compounds with the dominant composition being cyclopropyl with a concentration of 14.87%; acetic acid with a concentration of 17.01%; benzenesulfonic acid with a concentration of 12.11%; benzene with a concentration of 7.3% and phenol with a concentration of 15.59%.The characterization of the composition of the organic palm shell charcoal organic compounds needs to be done in order to about the development of the use of oil palm shell charcoal as an auxiliary material to increase plant fertility.